Educational Governance Based on Heart Management at Negeri Elementary School 173529 Tampahan, Toba Regency - Rosalinda Septiani Sitompul; Binur Panjaitan (Jurnal Mantik, 2022)
Education is an activity to educate a nation. Formal education is a tiered and structured education consisting of basic education, secondary education and higher education. Educational institutions (schools) must be managed properly, so that the goals of school education can be achieved. The purpose of this study was to determine how the management of education based on heart management at SD Negeri 173529 Tampahan, Toba Regency. Data collection techniques were carried out by observation and interviews. The data analysis technique was carried out by qualitative descriptive analysis. The results of the study are that in school management, leadership is needed from a school principal. In addition to leadership, a school principal becomes an innovator, motivator and entrepreneur (entrepreneur). In management, innovation in management of the heart is also needed,